Investigation of glucose-insulin model efficacy for diabetes patient in the ICU - Abdul Razak A.; Abu-Samah A.; Razak N.N.; Ahamad N.; M. Suhaimi F.; Jamaludin U.K.; Md Ralib A.; Mat-Nor M.B. (Springer Verlag, 2023)
Biomedical engineering; Blood; Errors; Glucose; Insulin; Medical problems; Blood glucose; Critically-ill patients; Fitting error; Influential factors; Inter-relationships; Malaysians; Model-based OPC; Real time modeling; Patient treatment